Isolated Renal Cyst Hydatic: A Rare Case Report - Özer, Aslı; Koc, Mustafa (My University, 2024)
Hydatid cyst is a parasitic disease caused by Echinococcus granolosus. It is occurred by orally ingested larvae that invade the mucosa of the small intestine and settle in organs through the blood and lymph circulation. It is still a serious public health problem in endemic areas such as the Mediterranean basin. It is frequently seen in India, Africa, South America, Central European countries and Turkiye. It is most commonly found in the liver (75%) and lungs (15%). Although the incidence of genitourinary involvement is approximately 2-4%, isolated renal involvement is extremely rare with 2%. In this article, we present the computed tomography imaging findings of an incidental case of isolated unilateral hydatid cyst.
Keywords: Renal; computed tomography; ultrasonography; Hydatid cyst